2003
DOI: 10.1097/01.ta.0000046252.97590.be
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Intubation in the Field Does Not Improve Outcome in Trauma Patients Who Present without an Acutely Lethal Traumatic Brain Injury

Abstract: Prehospital intubation is associated with a significant increase in morbidity and mortality in trauma patients with traumatic brain injury who are admitted to the hospital without an acutely lethal injury. A randomized, prospective study is warranted to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
104
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(118 citation statements)
references
References 9 publications
6
104
0
8
Order By: Relevance
“…Recent literature has questioned the safety and benefit of out-of-hospital intubation in certain patients, particularly the headinjured trauma patient. 6,7 Two studies also found rates of misplaced ETTs that ranged from unacceptable (25%) 8 to concerning but more in line with earlier literature (5.8%) 9 using hospital rather than field verification of proper placement. Before we determine the true impact of an out-of-hospital intervention on patient outcomes, we need to know whether, and in what settings, the intervention can be performed.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Recent literature has questioned the safety and benefit of out-of-hospital intubation in certain patients, particularly the headinjured trauma patient. 6,7 Two studies also found rates of misplaced ETTs that ranged from unacceptable (25%) 8 to concerning but more in line with earlier literature (5.8%) 9 using hospital rather than field verification of proper placement. Before we determine the true impact of an out-of-hospital intervention on patient outcomes, we need to know whether, and in what settings, the intervention can be performed.…”
supporting
confidence: 67%
“…8 Several studies have also questioned the effect of out-of-hospital intubation on patient outcomes, particularly in the head-injured patient. 6,7,13 Given the discrepancy in the literature and the potential impact on patient care, a clear understanding of success and complication rates related to airway management is crucial to effectively establish protocols for EMS systems. We present the success and complications rates of intubation in a highvolume, urban 9-1-1 system.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] EADs are the most common alternative to intubation in the field and likely the most common rescue airway device for failed intubation, other than bag-mask ventilation. The placement of an EAD can occur quickly, provides a means to oxygenate and ventilate a patient, and in many systems falls within the scope of practice for If the EAD does decrease cerebral perfusion-particularly in patients in a low-flow state-then many of these benefits of EAD placement may be outweighed by increased morbidity and mortality, although this has not been definitively demonstrated by research to date.…”
Section: Discussionmentioning
confidence: 99%
“…5). Three studies 7 30 36 reported on pneumonia after pre-hospital or in-hospital intubation; it was the primary study outcome in In-hospital mortality Suominen and colleagues 29 Sloane and colleagues 30 Winchell and colleagues 31 Gausche and colleagues 32 Murray and colleagues 33 Cooper and colleagues 34 Davis and colleagues 35 Bochicchio and colleagues 36 DiRusso and colleagues 37 Wang and colleagues 38 Davis and colleagues 39 Davis and colleagues 28 Klemen and Grmec 40 1 h mortality von Elm et al …”
Section: Harm Outcomesmentioning
confidence: 99%
“…Sloane and colleagues 30 Bochicchio and colleagues 36 Eckert and colleagues 7 Inadvertent hyperventilation…”
Section: Pneumoniamentioning
confidence: 99%